Interparliamentary relations and the future of devolution in the UK 1998-2018 : unravelling threads? - Arnott, Margaret A. (Emerald points., 2024)
Interparliamentary Relations and the Future of Devolution in the UK provides a political analysis of interparliamentary relations at a time when devolved legislatures are more evidently asserting their influence. Chapters provide the context necessary to understanding current complexities, considering the future of UK politics in response to critical circumstances such as Brexit and the Covid-19 pandemic. Margaret Arnott recognises how tensions between competing narratives about the future working of devolution in the UK, particularly over the future relationship of the devolved nations to the UK, were all too evident in contemporary political narratives. Written at a time of intensified political debates and the increasing questioning of models of democracy, Interparliamentary Relations and the Future of Devolution in the UK addresses a significant gap in academic literature to consider both the collective future of UK governance and that of the individual nations who form it.